Classification of Lipschitz mappings - Piasecki, Łukasz (Pure and applied mathematics, 2014)
'Classification of Lipschitz Mappings' presents a systematic, self-contained treatment of a new classification of Lipschitz mappings and its application in many topics of metric fixed point theory. Suitable for readers interested in metric fixed point theory, differential equations, and dynamical systems, the book only requires a basic background in functional analysis and topology. The author focuses on a more precise classification of Lipschitzian mappings--